Tourisme, sports de nature et développement durable aux Seychelles - Olivier Naria; Kenneth Sherwin M.D (Études Caribéennes)
The Republic of Seychelles is made of more than 115 small islands in the Indian Ocean, with 455 km2 of land in a stretch of about 1200 km. The three biggest inner islands are Mahe, Praslin, and La Digue, which include about 95% of the population. The Seychelles islands give the possibility in optimal conditions a vast variety of tourism activities and nature sports all year long, due to their geographical situations, their geomorphological configurations, their climate particularities, and their attractive images of touristic destinations. Walking and equestrian trekking, mountain bike, climbing, surfing, diving, yachting, and canoe-kayaking are some activities available in this insular territory. Because of this exceptional potential, the development of “nature” sports is in the (universe) field of leisure and tourism. The objective of this study is to identify what place “nature” sport activities play in the tourism offer in the Seychelles. Don’t they contribute, in the long-term development of the islands by having relations more interactive with the economic activity, the territorial structure, and the identity construction? Is the outcome of long-term development taken seriously by the actors of Seychelles in tourism field?